A comparative study of bacterial colony counts and Enterobacteriaceae isolates in pregnant women across pregnancy trimesters - Suwanto, Yustiana Arie; Suryani , Annisa Saffana Azmi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Urinary tract infections (UTIs) are common during pregnancy and may lead to serious complications for both mother and foetus. Anatomical and hormonal changes throughout gestation, particularly bladder compression and urinary stasis, create favourable conditions for bacterial colonisation and subsequent infection. Escherichia coli and other Enterobacteriaceae are the predominant pathogens, and urine culture remains the definitive diagnostic method, with a threshold of ≥10⁵ CFU/mL indicating infection. The objective of this study is to investigate the prevalence and distribution of bacterial colony counts and the presence of Enterobacteriaceae in pregnant women across all trimesters, as well as to assess the relationship between gestational age, bacterial load, and the incidence of UTIs. This observational cross-sectional study involved 46 pregnant women at various gestational stages. Midstream random urine samples were collected and subjected to microbiological culture. The number of colony-forming units per millilitre (CFU/mL) and the species of bacteria isolated were recorded and analysed descriptively. UTIs was identified in 9 out of 46 participants (19.6%), characterised by bacterial counts ≥10⁵ CFU/mL. The trimester-specific prevalence showed that 11% of cases occurred in the first trimester, 33% in the second trimester, and 56% in the third trimester. The most frequently isolated pathogens were Escherichia coli (80%), Staphylococcus spp. (75%), Enterococcus spp. (25%), and Klebsiella pneumoniae (20%). UTIs were more prevalent in the later stages of pregnancy, with the third trimester showing the highest incidence. E. coli remained the leading uropathogen. These findings underscore the importance of early screening through urine culture to prevent adverse maternal and neonatal outcomes, particularly during the third trimester.